Visualization, understanding, and mitigation of process-induced-membrane irregularities in gas diffusion electrode-based polymer electrolyte membrane fuel cells. (19th April 2021) - Wang, Min; Medina, Samantha; Ochoa-Lozano, Josias; Mauger, Scott; Pylypenko, Svitlana; Ulsh, Michael; Bender, Guido
Abstract: Polymer electrolyte membrane fuel cells (PEMFC) show substantial promise for their application in electric vehicles. For large-scale manufacturing of PEMFCs, roll-to-roll coated gas-diffusion-electrodes (GDE) offer certain advantages over other production pathways. Procedures including hot pressing and coating an ionomer overlayer may be necessary for this manufacturing pathway to enable a suitable catalyst layer/membrane interface. The same procedures may potentially introduce membrane irregularities, especially when thin membranes are used. Limited understanding exists regarding if and to what extent such irregularities impact PEMFC performance and lifetime, and therefore be considered defects. In this study, NREL's customized fuel cell hardware that enables quasi in-situ infrared (IR) thermography studies was utilized to visualize spatial hydrogen crossover and identify membrane irregularities that originated from the GDE-based MEA fabrication process. The structure of these membrane irregularities was investigated by scanning electron microscopy (SEM) and its impact on initial H2 /air performance was determined. Accelerated stress testing (AST) revealed that these irregularities develop into failure point locations. These results were validated across many MEAs with identified process-induced membrane irregularities. By selecting specific gas diffusion media properties and by fine tuning the MEA hot pressing parameters, the formation of such membrane irregularities was mitigated. Graphical abstract: Image 1 Highlights: Visualized process-induced morphology changes (PIMs) by IR thermography. Elucidated structure & formation mechanism of PIMs by cross-sectional SEM. Studied impact of fabrication conditions on PIMs and initial performance. Fine tuning fabrication conditions mitigates PIMs in MEA. PIMs are seed points for AST failure, and shorten MEA lifetime.